Pengaruh Penambahan Ellagic Acid pada Karbonat Apatit terhadap Jumlah Sel Makrofag pada Proses Penyembuhan Defek Tulang - Nurmala Dewi, Aulia; Septommy, Catur; Setiawati, Herautami Caezar Yulia; Primasari, Dyah Noviana; Efrata, Eka Resti (Fakultas Kedokteran Gigi IIK Bhakti Wiyata, Kediri., 2024)
Background: Bone defects are a problem that can occur in the field of dentistry such as sockets after tooth extraction and periodontitis. The therapy that must be used in cases of bone defects is to use a bone graft. Apatite carbonate is a calcium phosphate biomaterial that has biocompatibility, bioactivity and osteoconductive properties. Ellagic acid is a phenolic compound that can provide anti-inflammatory effects, when applied to scars it can reduce macrophage cells by inhibiting the expression of pro-inflammatory cytokines IL-1 and TNF-α and stimulating anti-inflammatory cytokines and growth factors TGF-B and VEGF. Objective: To determine the effect of adding ellagic acid to carbonic apatite on the number of macrophage cells in the healing process of bone defects. Methods: This type of laboratory experimental research with the Post Test Only Control group design. The research sample used 21 male Wistar rats which were divided into 3 treatment groups, namely group 1 was treated with PEG, group 2 was treated with CHA and group 3 was given CHA + EA. Observation of the number of macrophages was carried out on the 5th day. Data analysis used Oneway Anova and continued with the LSD test. Results: the one-way Annova test yielded a sig 0.00 (p <0.05) indicating that overall there was a significant difference. The results of the LSD test showed significant differences between the study groups. Conclusion: The addition of ellagic acid to carbonic apatite affects the number of macrophage cells in the healing process of bone defects in Wistar rats (Rattus novergicus). Keywords: Juice macrophage cells, ellagic acid and carbonic apatite